EFEKTIVITAS EKSTRAKURIKULER PRAMUKA DALAM PENGEMBANGAN KARAKTER PESERTA DIDIK DI MI ASH-SHALIHIN KABUPATEN GOWA - Alfairani Irwan, Dila; Sulaiman, Umar; Syamsudduha, St. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: 1) describe the implementation of scout extracurricular activities at MI Ash-Shalihin Gowa Regency, 2) describe the disciplinary and responsible character of students at MI Ash-Shalihin Gowa Regency, and 3) examine whether scout extracurricular activities are effective in developing student character at MI Ash-Shalihin Gowa Regency. This research employs a quantitative approach with ex post facto design. The population consisted of all students at MI Ash-Shalihin, with a sample of 37 students selected using purposive sampling technique. Data were collected using Likert-scale questionnaires, while data analysis utilized descriptive and inferential statistics, including simple linear regression to test the research hypothesis and effectiveness level analysis to measure the effectiveness of scout extracurricular activities in developing student character. The results showed that: 1) the implementation of scout extracurricular activities at MI Ash-Shalihin Gowa Regency was in the moderate category with a percentage of 75.66%, 2) the disciplinary and responsible character of students was in the moderate category with a percentage of 67.57%, and 3) scout extracurricular activities had a significant effect on student character development at MI Ash-Shalihin Gowa Regency, indicated by a significance value of 0.000 < 0.05, thus H₀ was rejected and H₁ was accepted. Furthermore, the effectiveness level calculation showed a percentage of 79.45%, falling into the quite effective category. Therefore, scout extracurricular activities are quite effective in developing the disciplinary and responsible character of students at MI Ash-Shalihin Gowa Regency.